2004
DOI: 10.1016/j.autrev.2004.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Anti-laminin-1 autoantibodies, pregnancy loss and endometriosis

Abstract: Laminin-1 is a major component and multifunctional glycoprotein of basement membranes that consists of three different subunits, a1, b1 and g1 chains. It is the earliest synthesized network-forming protein during embryogenesis and plays an important role in embryonic development, embryonic implantation and placentation. We have recently shown that IgG anti-laminin-1 antibodies were significantly associated with recurrent first-trimester miscarriages and with subsequent pregnancy outcome. Interestingly, these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Anti-laminin antibodies are detected in murine and human SLE, including among a subset of crossreactive anti-DNA Ig, and may mediate BM binding [199202]. Anti-laminin autoantibodies have been associated with Raynaud’s phenomenon, cardiomyopathy, pregnancy loss, and psoriasis in man [203205]. Pathogenic potential of anti-laminin IgG is suggested by induction of proteinuria and glomerular BM alterations in rats after passive transfer of anti-laminin Ig [206], and by the ability of laminin peptides to suppress lupus nephritis in MRL/lpr mice [207].…”
Section: Bm Autoimmunity In Additional Clinical and Experimental Settmentioning
confidence: 99%
“…Anti-laminin antibodies are detected in murine and human SLE, including among a subset of crossreactive anti-DNA Ig, and may mediate BM binding [199202]. Anti-laminin autoantibodies have been associated with Raynaud’s phenomenon, cardiomyopathy, pregnancy loss, and psoriasis in man [203205]. Pathogenic potential of anti-laminin IgG is suggested by induction of proteinuria and glomerular BM alterations in rats after passive transfer of anti-laminin Ig [206], and by the ability of laminin peptides to suppress lupus nephritis in MRL/lpr mice [207].…”
Section: Bm Autoimmunity In Additional Clinical and Experimental Settmentioning
confidence: 99%
“…18 In humans, elevated LM-111 expression was described in endometriotic lesions and anti-LM-111 autoantibodies were found in infertile patients. 19 Enhanced expression of LM-111 was also reported in astrocytes of diseased areas in the frontal cortex of Alzheimer's brain tissues, 20 and reduced expression was observed in acinar basement membranes of patients with Sjögren's syndrome, 21 indicating that LM expression patterns change during pathological processes.…”
mentioning
confidence: 96%
“…Among the various auto-Abs described (9)(10), recently aLN-1 have gained more attention due to their significantly higher prevalence in patients with endometriosis when compared with infertile patients without endometriosis (11). It has been suggested that aLN-1 affect early reproductive processes, leading to autoimmune-mediated infertility (12)(13).…”
mentioning
confidence: 99%